DNA-encoded dynamic hydrogels for 3D bioprinted cartilage organoids - Ziyu Chen; Hao Zhang; Jingtao Huang; Weizong Weng; Zhen Geng; Mengmeng Li; Jiacan Su (Materials Today Bio)
Articular cartilage, composed of chondrocytes within a dynamic viscoelastic matrix, has limited self-repair capacity, posing a significant challenge for regeneration. Constructing high-fidelity cartilage organoids through three-dimensional (3D) bioprinting to replicate the structure and physiological functions of cartilage is crucial for regenerative medicine, drug screening, and disease modeling. However, commonly used matrix bioinks lack reversible cross-linking and precise controllability, hindering dynamic cellular regulation. Thus, encoding bioinks adaptive for cultivating cartilage organoids is an attractive idea. DNA, with its ability to be intricately encoded and reversibly cross-linked into hydrogels, offers precise manipulation at both molecular and spatial structural levels. This endows the hydrogels with viscoelasticity, printability, cell recognition, and stimuli responsiveness. This paper elaborates on strategies to encode bioink via DNA, emphasizing the regulation of predictable dynamic properties and the resulting interactions with cell behavior. The significance of these interactions for the construction of cartilage organoids is highlighted. Finally, we discuss the challenges and future prospects of using DNA-encoded hydrogels for 3D bioprinted cartilage organoids, underscoring their potential impact on advancing biomedical applications.